Teachers' Self-Efficacy and Professional Competence in Writing HOTS Questions Through In-House Training - Pujiastuti, Lita; Cathrin, Shely; Wati, Unik Ambar (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study addresses the significance of Higher Order Thinking Skills (HOTS) in equipping students for the challenges of Society 5.0. It evaluates the effectiveness of In-House Training (IHT) in improving teachers' competence in designing HOTS-based questions. A School Action Research (SAR) design was employed, consisting of two cycles. The study involved eight teachers selected based on availability and specific study needs. Data were collected using observation and questionnaire methods. Observations assessed teachers' ability to develop HOTS questions, while questionnaires measured their self-efficacy. The findings demonstrated a notable improvement in teachers' ability to create HOTS questions. The average score increased from 68.75 in the first cycle to 86.25 in the second cycle. Similarly, teachers' self-efficacy showed improvement, with mean scores rising from 3.63 in cycle I to 3.96 in cycle II. The results suggest that IHT was effective in enhancing teachers' knowledge, skills, and confidence in developing HOTS-based questions. The significant increase in both HOTS question development and self-efficacy between cycles indicates the training’s success in building teacher competence. In-House Training (IHT) is an effective strategy for improving teachers' ability to design HOTS questions, which are essential for preparing students to meet the demands of Society 5.0. Further research could explore the long-term impacts of IHT on teacher performance and student outcomes.